Comparing the Concept of Ideal State Through the Lens of al-Farabi’s and Augustine’s Perspectives - Sudarman, Sudarman (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2020)
This research is a comparative analysis over the concept of an ideal state according to the perspective of a Muslim philosopher, Al-Farabi and that of a Christian philosopher, Augustine. It is an interfaith study that is based on a library research. The main data are collected through the book of Arā 'Ahl al-Madīnah al-Fādilah by al-Farabi and The City of God, by Agustinus, before they are analyzed with a hermeneutic approach. It argues that there are some similarities between Al-Farabi’s and Augustine's thoughts on the concept of ideal state, as well as a few differences. According to al-Farabi, an ideal state is the one that is led by a prophet or a philosopher, because, like the heart in a human body, the leader occupies a central position and is highly decisive. An ideal state according to Augustine refers to the concept of the city of God or the heavenly city, which is resided by innocent people, or sinners who have received God’s repentance. In this regards, the opposite of the City of God is the City of Man, in which all sinners are living their lives.